Electro‐Oxidation of Ni42 Steel: A Highly Active Bifunctional Electrocatalyst. (5th July 2016) - Schäfer, Helmut; Chevrier, Daniel M.; Zhang, Peng; Stangl, Johannes; Müller‐Buschbaum, Klaus; Hardege, Jörg D.; Kuepper, Karsten; Wollschläger, Joachim; Krupp, Ulrich; Dühnen, Simon; Steinhart, Martin; Walder, Lorenz; et al.
Abstract : Janus type water‐splitting catalysts have attracted highest attention as a tool of choice for solar to fuel conversion. AISI Ni42 steel is upon harsh anodization converted into a bifunctional electrocatalyst. Oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are highly efficiently and steadfast catalyzed at pH 7, 13, 14, 14.6 (OER) and at pH 0, 1, 13, 14, 14.6 (HER), respectively. The current density taken from long‐term OER measurements in pH 7 buffer solution upon the electro‐activated steel at 491 mV overpotential ( η ) is around four times higher (4 mA cm −2 ) in comparison with recently developed OER electrocatalysts. The very strong voltage–current behavior of the catalyst shown in OER polarization experiments at both pH 7 and at pH 13 are even superior to those known for IrO2 ‐RuO2 . No degradation of the catalyst is detected even when conditions close to standard industrial operations are applied to the catalyst. A stable Ni‐, Fe‐oxide based passivating layer sufficiently protects the bare metal for further oxidation. Quantitative charge to oxygen (OER) and charge to hydrogen (HER) conversion are confirmed. High‐resolution XPS spectra show that most likely γ−NiO(OH) and FeO(OH) are the catalytic active OER and NiO is the catalytic active HER species. Abstract : Harsh anodization has converted relatively less catalytically active untreated Ni42 steel into an outstanding bifunctional electrocatalyst (Ni42‐300). The oxygen evolution reaction (OER) and hydrogen evolution reaction (HER) are highly efficiently and steadfast catalyzed at pH 7, 13, 14, 14.6 (OER) and at pH 0, 1, 13, 14, 14.6 (HER), respectively. Ni42‐300 can be utilized as electrodes in electrolyzers with bipolar cell configuration.